2022
DOI: 10.1038/s41419-022-04835-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calcium uptake regulates tumour progression in embryonal rhabdomyosarcoma

Abstract: Embryonal rhabdomyosarcoma (ERMS) is characterised by a failure of cells to complete skeletal muscle differentiation. Although ERMS cells are vulnerable to oxidative stress, the relevance of mitochondrial calcium homoeostasis in oncogenesis is unclear. Here, we show that ERMS cell lines as well as primary tumours exhibit elevated expression of the mitochondrial calcium uniporter (MCU). MCU knockdown resulted in impaired mitochondrial calcium uptake and a reduction in mitochondrial reactive oxygen species (mROS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…To investigate mechanisms of calcification that may primarily rely on mitochondria, we used the rhabdomyosarcoma cell line RH30, which has metabolically functional mitochondria [ 21 , 30 ]. Given that calcium deposits of JDM calcinosis are primarily of HA in nature [ 4 , 5 ], we quantified calcium phosphate complexes in RH30 cells using Osteoimage ™ [ 31 ], a fluorescent staining reagent highly specific for HA as represented in the schematic ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate mechanisms of calcification that may primarily rely on mitochondria, we used the rhabdomyosarcoma cell line RH30, which has metabolically functional mitochondria [ 21 , 30 ]. Given that calcium deposits of JDM calcinosis are primarily of HA in nature [ 4 , 5 ], we quantified calcium phosphate complexes in RH30 cells using Osteoimage ™ [ 31 ], a fluorescent staining reagent highly specific for HA as represented in the schematic ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, mtCa 2+ uptake was found to be critical in embryonal rhabdomyosarcoma (ERMS). Indeed, MCU expression is upregulated in ERMS, and its downregulation causes mROS level decreases and an increased propensity to differentiate, inhibiting the oncogenic phenotype [ 92 ].…”
Section: Skeletal Muscle Diseasesmentioning
confidence: 99%
“…5 c,d). As mitochondrial calcium is known to modulate respiration [39], we also analysed whether Bax/Bak deficiency affects cellular and mitochondrial calcium levels, and found that calcium levels were, in contrast to parental cells, maintained in Bax/Bak-deficient U87 cells challenged with calcium-free cerebrospinal fluid (aCSF) (Suppl. Fig.…”
Section: Elimination Of Bax and Bak Leads To Cell-type Specific Effec...mentioning
confidence: 99%